Religious Architecture and Urbanism in Vigo During José Delicado Baeza’s Episcopate (1969-1975) - Esteban Fernández-Cobián; Marta Vilas Rodríguez (Histories of Postwar Architecture)
During the 1950s and 1960s, there was a significant urban expansion across much of Europe. Following the end of World War II, the migration of people from rural areas to cities became widespread. New job opportunities arising from industrialization and service sectors, coupled with the pursuit of a higher standard of living, were among the driving forces behind this mass exodus. Cities had to quickly adapt, multiplying infrastructures, generating residential areas, and giving rise to spaces for social interaction and leisure for the new workforce – known as facilities or amenities – which risked being relocated after leaving their places of origin. Religious facilities were among the first to emerge. Within the Catholic Church sphere, the efforts of various European ecclesiastical leaders, in countries such as France, Germany, and Italy, are well-known in this regard. This article highlights the work of Bishop José Delicado Baeza, who during his brief tenure in the Spanish diocese of Tui-Vigo (1969-75) undertook a profound territorial reform that multiplied parish jurisdictions in a city undergoing rapid urban expansion. To this end, previously unpublished documentation from diocesan and municipal archives, as well as from the professional archives of the main architects who collaborated in the construction of churches, has been utilized.